Physical Entities and Spatiotemporal Junk. a Critical Reconstruction of P. Dowe S Physical Ontology - Quezada-Pulido, W; Pavez-Flores, L (UNIV EL BOSQUE, 2024)
A classic challenge for any theory of physical causation based on conserved quantities and formulated within the framework of special relativity theory, has been to distinguish two regions, that of genuine causal relationships and that of those spurious or noncausal ones. In the causal processes theory defended by P. Dowe, this is done by introducing a criterion based on the possession of a conserved quantity, which would seem to efficiently demarcate between causal processes and causal pseudoprocesses. However, faced with criticism about the inadequacy of his criteria, Dowe has proposed modifying his physical ontology and introducing, along with processes and pseudo-processes, two types of physical gerrymander entities, both temporal and spatial. In this article, we analyze and criticize, from the perspective of ERT, Dowe s characterization of these quasi-entities and the theoretical need to make a clear-cut distinction between them. This implies a fundamental modification of Dowe s ontology and raises other doubts about its original motivation.